Possible dialogues between Linguistics of Enunciation and Ecolinguistics - Assis, Mayara Macedo; Couto, Elza Kioko Nakayama Nenoki do (Revista Letras Raras, 2022)
This article aims to analyze the possible dialogues between Linguistics of Enunciation and Ecolinguistics, considering mainly the studies of Benveniste and Bakhtin, in the field of Enunciation, and Couto, in the field of Ecolinguistics, especially Ecosystemic Linguistics. This interrelation is proposed since both fields represented a great change in what was being done until their emergence, offering new ways of studying and seeing linguistic phenomena, therefore, they present some points in which they differ and others that they have in common. Thus, one can notice the presence of enunciation theories traces in the presuppositions of Ecolinguistics/Ecosystemic Linguistics, despite the fact that the latter has reworked the concepts and presented a reformulated perspective. The relationship between the theoretical fields is related to the ecology of communicative interaction. However, Ecosystem Linguistics innovates more in the sense of looking at its object in its entirety and not seeing language as the realization of a system that produces a text, but rather as a (communicative) interaction between two people. The whole of the dialogue is emphasized, not just its product.